EFL TEACHERS CHALLENGES IN DEVELOPING INTERACTIVE TEACHING MATERIAL FOR SENIOR HIGH SCHOOL STUDENTS - Rahman, Ali Wira; Indahyanti, Rizka; Nur, Sahril (English Education Journal, 2024)
This study investigates the challenges faced by English as a Foreign Language (EFL) teachers in developing interactive teaching materials for senior high school students. A qualitative approach was adopted, using a questionnaire distributed to 11 EFL teachers in senior high schools in Makassar. The questionnaire explored their experiences, challenges, and needs in developing interactive teaching materials. The findings reveal significant challenges, including limited access to technology, time constraints, and insufficient training. There are some recommendations that include in this study namely enhancing professional development programs, increasing access to resources, and addressing administrative workloads to enable teachers to create more engaging and effective materials.